2020
DOI: 10.3390/pr8091149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Regenerated Cellulose Fibers Derived from Black Oat on Functional Properties of PVA-Based Biocomposite Film

Abstract: In this study, agricultural residue from black oat, a cover crop usually grown to improve soil nutrients between the periods of regular crop production, was used as a source of cellulose fibers. Concentrations of 1, 3, and 5 wt. % of regenerated cellulose (RC) fibers blended in poly(vinyl alcohol) (PVA) solution were used to prepare the reinforced composite films (CFs) by the solvent cast method. Compared to neat PVA film (control), the effects of RC addition on functional properties of CFs, such as water abso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In another study, Shahi et al [276] demonstrated the possibility of producing a biocomposite film (PVA-RC) based on regenerated cellulose fibers isolated from black oat and PVA (polyvinyl alcohol). It has been demonstrated that regenerated oat cellulose fibers are well dispersed in the polymer mixture and demonstrate good PVA/nanocellulose compatibility due to the formation of hydrogen bonds.…”
Section: Nanocrystal Cellulosementioning
confidence: 99%
“…In another study, Shahi et al [276] demonstrated the possibility of producing a biocomposite film (PVA-RC) based on regenerated cellulose fibers isolated from black oat and PVA (polyvinyl alcohol). It has been demonstrated that regenerated oat cellulose fibers are well dispersed in the polymer mixture and demonstrate good PVA/nanocellulose compatibility due to the formation of hydrogen bonds.…”
Section: Nanocrystal Cellulosementioning
confidence: 99%
“…It is notable that the water uptake properties of the PVA-3, which was approximately 89% as indicated in Table 2, were superior compared to the published studies. The percentage of water uptake, also known as the swelling ratio, 44 of PVA/ regenerated cellulose film produced by Shahi et al was between 35 to 40% after being immersed in water for 24 h. PVA/ banana pseudostem fiber (BPF) film produced by Srivastava et al 45 exhibited 67.4% swelling. The high-water update in this study was due to the use of starch, which can hold water via hydrogen bonding.…”
Section: Performance Of Starch/cellulose/polyvinyl Alcohol Filmsmentioning
confidence: 99%
“…The ability of cellulose to immobilize dyes also exhibits a uniform dyes’ distribution on the RC film for high detection of heavy metal ions that are present in the irrigation water source [ 174 ]. Other than being an immobilization particle for the dyes employed in chemical sensors, cellulose is often being reinforced by other biodegradable synthetic polymers such as polyvinyl alcohol (PVA) to form flexible sensor film because of massive amorphous region of cellulose have aided in enhancing mechanical strength and optical transparency [ 186 ]. The humidity level of soil or moisture of the soil is a pivotal parameter to be monitored to yield quality crops.…”
Section: The Potential Applications Of Regenerated Cellulose Products For Agriculturementioning
confidence: 99%